Cardiovascular disease as a complication of community-acquired pneumonia. Issue 3 (May 2016) - Rae, Nikolas; Finch, Simon; Chalmers, James D.
Abstract : Purpose of review: Here, we review the incidence, prognosis, potential mechanisms and therapeutic implications of cardiovascular disease in community-acquired pneumonia (CAP). Recent findings: Recent evidence suggests that a large proportion of deaths from CAP are attributable to cardiovascular disease, including sudden cardiac death, acute myocardial infarction (MI), arrhythmias and cardiac failure. Up to one-third of patients with CAP may experience cardiovascular complications within 30 days of hospital admission, while data also suggest that CAP managed in the community is associated with increased risk of acute MI. The risk is maximal within a few days of hospitalization with CAP and reduces over time. Most studies suggest that risk is still increased at 1 year, and some suggest risk continues to be increased at 10 years post-CAP. This clearly contributes to the well-recognized increased long-term mortality associated with CAP. The mechanism is not entirely clear, but recent published data have better defined the impact of the host response, including systemic inflammation and platelet activation. The contribution of Streptococcus pneumoniae has also been recently investigated, with animal studies suggesting a direct effect of S. pneumoniae on the myocardium, forming microlesions that heal with resulting myocardial fibrosis. Several studies suggest a key role for the pore-forming toxin pneumolysin in S. pneumoniae -induced cardiac toxicity. Summary: Several therapies have been shown to improve the outcomes in cardiovascular disease, but whether these would be effective in improving outcomes in CAP is unknown. In this review, we argue that cardioprotective treatments may hold the greatest promise in terms of reducing long-term mortality in patients with CAP.